Improving prehospital and emergency care for patients with mental dysregulation: a comprehensive research agenda - Galenkamp, Niek; van de Glind, Geurt; Schut, Bart; Baden, David; Singendonk, Maartje M J; Werner, Lente; van Veen, Mark; Schoonhoven, Lisette; Scheepers, Floortje E; Blom-Ham, Wietske H W (BioMed Central Ltd., 2026)
OBJECTIVE: To develop a research agenda on mental dysregulation in emergency care settings, that is informed and prioritized by patients' lived experiences, professional expertise from multiple emergency care domains, and the current state of science. METHODS: The Dialogue Model was employed to establish this research agenda. This approach is designed to promote equitable participation of patients and healthcare professionals in the research agenda-setting process. Within this model, a mixed-method approach was conducted, using secondary analysis of qualitative data, an online survey and interviews with key stakeholders, a literature review and a dialogue meeting. Key stakeholders were selected from all domains of the prehospital and emergency care system in the Netherlands, including persons with lived experience, nurses, physicians, mental health professionals and policymakers. RESULTS: A total of n = 29 key stakeholders were involved. A research agenda was developed which comprises two conditional themes (Understanding the scope and consequences of mental dysregulation in emergency care; Contact between healthcare professional and patient), three content themes (Support for emergency care professionals by teams and organizations; Adapting emergency care practices and environments to the needs of patients who experience mental dysregulation; Prevention of dysregulation and hospitalization in emergency care) and one organizational theme (Interdisciplinary collaboration around patients who experience mental dysregulation). CONCLUSIONS: With this research agenda valuable research priorities are provided, acknowledged and prioritized by patients with mental dysregulation and healthcare professionals in the emergency care setting. By involving key stakeholders in the process of developing this research agenda, it covers multiple perspectives and has led to a mutual understanding. As such, it provides a valuable viewpoint for the future direction of research and practice in this field.
Keywords: Journal Article